Role Mismatch in Medical Decision-Making Participation Is Associated with Anxiety and Depression in Family Members of Patients in the Intensive Care Unit - Tingting Fang; Pengfei Du; Yin Wang; Dandan Chen; Hailin Lu; Haoran Cheng; Wenqing Hu; Donghui Jiang (Journal of Tropical Medicine)
This study aimed to investigate the mismatch between the preferred and actual roles in the medical decision-making of intensive care unit (ICU) patients’ family members and the relationship between the role mismatch of family members’ decisions and anxiety and depression syndromes. A total of 223 family members of ICU patients in the Affiliated Hospital of Jiangnan University in China were enrolled. The simple Chinese version of the Control Preference Scale was used to complete the surveys to assess the preferred and actual roles, and anxiety and depression syndromes were measured using the Generalized Anxiety Disorder-7 scale and Patient Health Questionnaire-9, respectively. For the preferred and actual roles, the active role rates were 16.1% and 8.1%, the cooperative role rates were 49.3% and 31.4%, and the passive role rates were 34.5% and 60.5%, respectively. The incidence of mismatch was 43.0% between the preferred and actual roles, and the consistency between their preferred and actual decision-making roles was poor (kappa = 0.309, P < 0.001). Family members with mismatched decision-making roles had significantly higher incidence rates of anxiety (90.6% vs. 57.5%, P < 0.001) and depression (86.5% vs. 63.0%, P < 0.001). Logistic regression analysis revealed that mismatches in decision-making roles remained independently associated with these outcomes after adjustment for family members’ sociodemographic features. The results of the present study demonstrate that the preferred role of ICU patients’ family members is mainly cooperative, and the actual role is mainly passive. The mismatch between the preferred and actual roles is associated with anxiety and depression among the ICU patients’ family members.